Sensitivity and specificity of the body mass index for the diagnosis of overweight/obesity in elderly Sensibilidade e especificidade do índice de massa corporal no diagnóstico de sobrepeso/obesidade em idosos - Francisco de Assis Guedes de Vasconcelos; Braian Alves Cordeiro; Cassiano Ricardo Rech; Edio Luiz Petroski (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The aim of this article was to verify the sensitivity and specificity of the body mass index (BMI) cut-off points proposed by the World Health Organization (WHO) and the Nutrition Screening Initiative (NSI) for the diagnosis of obesity in the elderly. A cross-sectional study was made with 180 healthy elderly subjects from Florianópolis, Santa Catarina State, Brazil. Body fat percentage (%BF) was determined using DEXA (dual energy X-ray absorptiometry). The BMI cut-off point of the NSI offers better sensitivity and specificity for men (73.7% and 72.5% respectively). For women, the lower the cut-off point the better the sensitivity, with a BMI of 25kg/m² (sensitivity of 76.3% and specificity of 100%) being the most accurate for diagnosing obesity in elderly women. The WHO cut-off point offered very low sensitivity (28.9%). The results of this investigation lead to the conclusion that the cut-off points proposed by the WHO and the ones adopted by the NSI and by Lipschitz are not good indicators of obesity for the elderly of either sex, since they offer low sensitivity. O objetivo foi verificar a sensibilidade e especificidade dos pontos de corte do índice de massa corporal (IMC) propostos pela Organização Mundial da Saúde (OMS) e Nutrition Screening Initiative (NSI) no diagnóstico da obesidade em idosos. O estudo foi realizado com 180 idosos de Florianópolis, Santa Catarina, Brasil. O percentual de gordura corporal foi mensurado por absortometria radiológica de dupla energia. O IMC da NSI apresenta melhores valores de sensibilidade e especificidade para homens (73,7% e 72,5% respectivamente). Para os homens o IMC de 25kg/m² apresentou elevada sensibilidade (94,7%) e baixa especificidade (40%), enquanto o IMC de 30kg/m² possui baixa sensibilidade (31,6%) e elevada especificidade (97,5%). Nas mulheres, o IMC de 25kg/m² (sensibilidade de 76,3% e especificidade de 100%) foi o mais acurado. O ponto de corte da OMS mostrou sensibilidade muito baixa (28,9%). Os resultados desta investigação permitem concluir que os pontos de corte propostos pela OMS e NSI não são bons indicadores de sobrepeso/obesidade para idosos de ambos os sexos.